ANALISIS MINAT SISWA TERHADAP MATA PELAJARAN FISIKA DI SMA N 1 BATANGHARI - Sandari, Tiara (EduFisika: Jurnal Pendidikan Fisika, 2020)
Interesting in learning has influence on learning outcomes. If someone does not have an interest in a particular subject, it is difficult to achieve optimal learning outcomes. Conversely, if someone who has an interest in certain subjects will achieve optimal learning results.  Interesting will be formed if there is an effort from within him and there is also encouragement from the outside both from the teacher, family, and the surrounding environment to like, study and work on physics problems given by the teacher.  The purpose of this study was to determine students' interest in physics from the descriptions of the attitudes of SMA N 1 Batanghari students.  This type of research is quantitative using survey research procedures with the instrument used is a questionnaire.  The subjects of this study were 53 students of SMA N 1 Batanghari. The result of data analysis and discussion, it can be concluded that the learning interest of SMA N1 BATANGHARI students in physics lessons is good even though there are some students who are still less interested in learning.